2020
DOI: 10.1111/bjh.16380
|View full text |Cite
|
Sign up to set email alerts
|

Mutation‐enhanced international prognostic systems for essential thrombocythaemia and polycythaemia vera

Abstract: Survival prediction in essential thrombocythaemia (ET) and polycythaemia vera (PV) is currently based on clinically-derived variables; we examined the possibility of integrating genetic information for predicting survival. To this end, 906 molecularly-annotated patients (416 Mayo Clinic; 490 University of Florence, Italy), including 502 ET and 404 PV, were recruited. Multivariable analysis identified spliceosome mutations to adversely affect overall (SF3B1, SRSF2 in ET and SRSF2 in PV) and myelofibrosis-free (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
191
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 160 publications
(210 citation statements)
references
References 30 publications
6
191
0
2
Order By: Relevance
“…We also found that RUNX1 mutations were predictive of leukemic transformation. This nding is consistent with previous studies that demonstrated that RUNX1 mutations had adverse impacts on leukemia-free survival in PV and ET patients [16,17] and that RUNX1-mutated PMF patients had inferior overall survival and leukemia-free survival [35]. Another important gene was ASXL1; mutations in this gene are typically associated with brotic progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that RUNX1 mutations were predictive of leukemic transformation. This nding is consistent with previous studies that demonstrated that RUNX1 mutations had adverse impacts on leukemia-free survival in PV and ET patients [16,17] and that RUNX1-mutated PMF patients had inferior overall survival and leukemia-free survival [35]. Another important gene was ASXL1; mutations in this gene are typically associated with brotic progression.…”
Section: Discussionsupporting
confidence: 91%
“…Results of recent studies indicate that gene mutations are signi cant prognostic factors in MPN and mutation-enhanced prognostic systems for MPNs have been introduced [14][15][16]. These systems can be used to determine risk for survival as well as disease progression, including leukemic transformation and brotic progression [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also suggested the independent survival effect of adverse mutations, age >67 years, leukocyte count ≥15 × 10 9 /L, and previous thromboses in PV. A subsequent hazard ratio (HR)-based risk point allocation allowed the development of a three-tiered mutation-enhanced international prognostic system (MIPSS) whose performance was shown to be superior to other conventional scoring systems [39].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond cytopenias, as patients with MF live longer with the disease, clinicians have learned to manage other issues associated with long-term use of ruxolitinib, such as weight gain, hyperlipidemia and infectious risks. Improvements in our understanding of the molecular events underlying disease pathogenesis and progression, particularly the role of “non-driver” mutations, have not only enabled more refined prognostication [ 114 , 115 , 116 , 117 ], but may also inform therapeutic choices. For example, spleen response to ruxolitinib in MF is inversely correlated with the number of non-driver mutations; patients with ≥3 mutations have a shorter time to treatment discontinuation and OS than those with fewer mutations [ 118 ].…”
Section: Discussionmentioning
confidence: 99%